Design and validation of value-oriented strategic marketing model in Iranian airlines - Majid Ahang; Naser Azad; Abdullah Naami; Alireza Rousta (ارزش آفرینی در مدیریت کسب و کار)
Abstract The purpose of this research is to design and validate value-based strategic marketing model in Iranian airlines. In terms of purpose, the current research is applicable, and is a mixed research (qualitative-quantitative), and the philosophy of this research is positivistic-interpretative with an inductive approach. The statistical population of the research in the qualitative part includes 10 marketing specialists of airline companies and university professors with trends related to the research topic, selected by the purposeful sampling method and the snowball method. The statistical population of the quantitative part also includes 520 commercial and marketing specialists of airline companies, among whom a sample size of 221 were selected using Cochran's formula, and by stratified random sampling. The data collection tool includes a semi-structured interview in the qualitative part; and a researcher-made questionnaire in the quantitative part. Data analysis was done by the data method of the Corbin and Strauss Foundation (2015) and using MAXQDA (2020) software in the qualitative part; SPSS and AMOS software were used and in the quantitative part. The research model was extracted based on identifying 1015 open codes, relating the codes to 215 concepts and 31 main categories (in 12 categories). The results of the research, in addition to presenting a comprehensive and new model for strategic marketing for Iranian airlines with a value-based approach, showed that in order to have a dynamic and successful marketing and achieve the goals of profitability, customer satisfaction and economic development of the society, Iranian airlines should adopt marketing and development strategies. Extended Abstract Introduction Air travel creates many social and economic benefits for many different people, governments, national economies, large and small businesses, and travelers who simply want to visit family or enrich their lives by seeing new places and experiencing new cultures (IATA, 2022). The airline industry is one of the most competitive and capital intensive sectors in the world due to various factors such as low entry barriers and large number of airlines. This has led various airlines to propose or adopt strategies that help them gain a competitive advantage over their competitors (Garrett, 2019). Strategic marketing is the use of marketing disciplines to achieve organizational goals by developing and maintaining sustainable competitive advantage. It deals with high-level considerations, such as what markets to target, which services to offer, and how to price and promote them (Frederiksen, 2022). Researchers believe that the more organizations can gain a better understanding of customer needs as well as competitors' activities and factors affecting market conditions and information distribution at all levels of the organization, the more they will have the ability to survive in the competitive market. From a practical point of view, creating value for the customer becomes more important every day. Creating value for customers includes customer participatory behaviors and customer citizenship behaviors. Participatory behavior refers to the behavior and participation of customer information, accountability and personal interaction behaviors (Aroofarakh et al, 2023). Based on this, the current research is looking for an answer to this question: What is the design and validation of value-oriented strategic marketing model in Iranian airlines? Theoretical Framework Strategic marketing Current trends and forces in the 21st century encourage leading companies to define and apply comprehensive marketing concepts. Every decision and behavior in the framework of marketing activities is influenced by environmental factors. The most important feature of the environment is transformation and change. Strategic marketing is long-term marketing activities according to the marketing environment, which has long-term effects on the company and its future (Keller, 2017). Airlines It usually refers to an industry group that moves passengers or cargo through airlines. Airlines usually sell air tickets to their various destinations in a systematic way or allow them to create domestic and foreign tourism tours in the form of rental distribution between airline agencies (Halpern, 2022). Valorization The value creation process has moved from the traditional product and company-oriented perspective to the personal experiences of the consumer. Value creation and extraction is increasingly created through interactions between consumers and organizations, and value can be created through multiple elements such as price, quality, and location. Therefore, companies are responsible for determining the value delivered based on their strategies and shareholder values ​​(Tuominen & Matthyssens, 2022). Shadbakhsh (2023) investigated the impact of using sustainable marketing strategies on the performance of digital businesses with the mediation of information technology in the country's real estate industry. The results showed that marketing trends and sustainable marketing experiences have a positive effect on the performance of the studied companies. Also, marketing trends, sustainable marketing experiences and sustainable marketing strategies have a positive effect on the performance of selected companies. Wang (2021) has investigated the marketing strategies of Qatar Airways in a research titled "Understanding the strategy used by leading airlines". The results confirm that considering that the aviation industry is very competitive, it requires strong marketing strategies to create value and identify opportunities. The nature of services offered in the airline industry is attractive in terms of transportation, facilities, amenities and privileges. Companies must align themselves with specific segments or target customers based on capabilities and market dominance. Research methodology In terms of purpose, the current research is applicable, and is a mixed research (qualitative-quantitative); and the philosophy of this research is positivist-interpretative with an inductive approach. The statistical population of the research in the qualitative part includes 10 people from the marketing specialists of airline companies and university professors with trends related to the subject of the research, selected by the purposeful sampling method and the snowball method. The statistical population of the quantitative part also includes 520 commercial and marketing specialists of airline companies, among whom a sample size of 221 were selected using Cochran's formula and stratified random sampling. The data collection tool includes a semi-structured interview in the qualitative part, and a researcher-made questionnaire in the quantitative part. Research findings Data analysis was done through the data method of the Corbin and Strauss Foundation (2015) and using MAXQDA (2020) software in the qualitative part, and SPSS and AMOS software in the quantitative part. The research model was extracted based on identifying 1015 open codes; relating the codes to 215 concepts and 31 main categories (in 12 categories). The results of the research, in addition to presenting a comprehensive and new model for strategic marketing for Iranian airlines with a value-based approach, showed that in order to have a dynamic and successful marketing and achieve the goals of profitability, customer satisfaction and economic development of the society; Iranian airlines should adopt marketing strategies of development. Conclusion The current research was conducted with the aim of designing and validating value-based strategic marketing model in Iranian airlines. The results of this research are in agreement with the results of Gill (2020), Zhang (2020), Dini et al, (2018), Cobena et al, (2019), Wang (2021), Shafiei & Mirabi (2019), Camilleri (2018), Mikalef et al, (2020), IvyPanda (2021), Dewsnap et al, (2020), Day & Schoemaker (2020), Afshani & Hatefirad (2017), and Appel et al, (2020). Wang (2021) showed that considering that the aviation industry is very competitive, it requires strong marketing strategies to create value and identify opportunities. The nature of services offered in the airline industry is attractive in terms of transportation, facilities, amenities and privileges. Companies must align themselves with specific segments or target customers based on capabilities and market dominance. According to the results of the research, the following suggestions are provided: 1- It is suggested that Iranian airlines offer travel packages in the form of group and business trips with discounts on ticket prices and additional services such as carrying more luggage, boarding and disembarking from a separate gate, etc. This package aims to attract experts from industrial, commercial, academic groups, etc., who travel a lot, and can be effective in sales development. 2- In order to reduce costs caused by economic sanctions and improve the quality of airline services, it is suggested to cooperate with knowledge-based companies in the field of supplying and manufacturing aircraft consumable parts.